The J. William Fulbright memorial lectures, 1995-1996 - Cruz, Isagani R. (Philippine Fulbright Scholars Association, 1997)
It contains series of lectures by present or former university presidents. It provides knowledge to readers on speakers' insights into where the country is now and where it can go in the future.